A Review of Rare Disease Policies and Orphan Drug Reimbursement Systems in 12 Eurasian Countries - Czech, Marcin; Baran-Kooiker, Aleksandra; Atikeler, Kagan; Demirtshyan, Maria; Gaitova, Kamilla; Holownia-Voloskova, Malwina; Turcu-Stiolica, Adina; Kooiker, Coen; Piniazhko, Oresta; Konstandyan, Natella; Zalis'ka, Olha; Sykut-Cegielska, Jolanta (Frontiers in Public Health, 2020)
Background: Despite international initiatives on collaboration within the field of rare diseases, patient access to orphan medicinal products (OMPs) and healthcare services differ greatly between countries. This study aimed to create a comprehensive and in-depth overview of rare diseases policies and reimbursement of OMPs in a selection of 12 countries in the Western Eurasian region: Armenia, France, Germany, Kazakhstan, Latvia, The Netherlands, Poland, Romania, Russia, Turkey, Ukraine and the United Kingdom. Methods: A systematic literature review was performed and an analysis of publicly available legislative and rare disease health policy data was undertaken in 5 focus areas: rare disease definition, newborn screening, registries, national plans, access to/reimbursement of OMPs. Results: Screening programs are broadly implemented but the number of screened diseases differs significantly (2 to 35 diseases), either between EU and non-EU countries, between EU member states and sometimes even within a single country. In most countries rare disease registries are operating with regional, national, European or worldwide coverage. The number of rare disease registries is growing, as a result of the National Plans (EU) and increased international scientific cooperation. France, Russia and Poland have a centrally acting registry. National plans are present in all EU countries but implementation varies and is ongoing. The number of reimbursed OMPs in the selected EU members ranges from nearly all available OMPs in the Netherlands, Germany and France to zero in Armenia. A trend is observed of reimbursement conditions getting stricter for expensive (orphan) drugs, and reimbursement rules differ considerably regionally. Discussion: Inequality in patient access to new OMPs still exists due to variation in national policies, healthcare budgets, health insurance and reimbursement systems. The observed differences are challenging for rare disease patients, health authorities and manufacturers alike. Progress can be seen, however, and international cooperation and harmonization is slowly but steadily expanding in the rare disease arena.